2016
DOI: 10.1152/japplphysiol.00736.2016
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of measuring resting muscle sympathetic nerve activity using short sampling durations in healthy humans

Abstract: Resting muscle sympathetic nerve activity (MSNA) demonstrates high intraindividual reproducibility when sampled over 5-30 min epochs, although shorter sampling durations are commonly used before and during a stress to quantify sympathetic responsiveness. The purpose of the present study was to examine the intratest validity and reliability of MSNA sampled over 2 and 1 min and 30 and 15 s epoch durations. We retrospectively analyzed 68 resting fibular nerve microneurographic recordings obtained from 53 young, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 41 publications
(100 reference statements)
0
51
0
Order By: Relevance
“…Immediately following discrete brachial blood pressure measurements, cf‐PWV was measured at minute 7 and minute 9 during both baselines and at minute 9 and 11 during each pressure stimulus. In a subset of participants, continuous measures of MSNA were also collected over the entire duration of study to provide a direct marker of peripheral sympathetic activity 34, 35. To permit all variables to return to baseline levels, participants were given at least 8 minutes of quiet rest before repeating the protocol with the alternate pressure stimulus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately following discrete brachial blood pressure measurements, cf‐PWV was measured at minute 7 and minute 9 during both baselines and at minute 9 and 11 during each pressure stimulus. In a subset of participants, continuous measures of MSNA were also collected over the entire duration of study to provide a direct marker of peripheral sympathetic activity 34, 35. To permit all variables to return to baseline levels, participants were given at least 8 minutes of quiet rest before repeating the protocol with the alternate pressure stimulus.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm that the electrode site did not alter throughout the recording periods, the neural signal was monitored both audibly and visually. Custom semiautomated LabView software (National Instruments, Austin, TX) was used to quantify MSNA burst frequency (bursts/min), and total MSNA (AU/min) 34, 35. Total MSNA was calculated as the product of mean burst area × burst frequency; as each participant acted as their own control, we did not normalize the mean burst area data.…”
Section: Methodsmentioning
confidence: 99%
“…Efferent postganglionic multi-unit MSNA was recorded from the right fibular nerve as previously described (Millar et al, 2013; Notay et al, 2016). Briefly, the path of the fibular nerve, posterior to the fibular head, was marked using palpation and transdermal electrical simulation (Grass Technologies, Warwick, RI).…”
Section: Methodsmentioning
confidence: 99%
“…The integrated neurogram was analyzed using custom LabView software (Millar et al, 2013, 2015; Notarius et al, 2014; Notay et al, 2016) and reported as MSNA burst frequency (bursts/min), burst incidence (bursts/100 heartbeats), and normalized mean burst amplitude (% of maximum) and area (% of maximum). As MSNA burst amplitude and area are influenced by the proximity of the recording electrode to the discharging fibers, we normalized the data as a percentage of the largest burst amplitude and area, respectively, within each 4 min trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation